The public health veterinarian and food safety challenge (2008)
Veterinarians bring a broad combination of knowledge and skills to the interdisciplinary farm-to-table public health team and are qualified by a broad biological education and experience to deal in a wide range of areas important to food safety. Food safely is a scientific discipline describing the handling preparation, and storage of food in ways that prevent food-borne illness. In the United States, the Department of Agriculture's (USDA's) Food Safety and Inspection Service (FSIS) is the public health agency responsible for ensuring that the nation’s commercial supply of meat, poultry, and egg products is safe, wholesome, and correctly labeled and packaged. In Nigeria, two military decrees- the Animal Disease Control Act (Decree 10) of 1988 and the revised National Food and Drug Administration and Control NAFDAC decree of 1999 regulate and control medical and food safely matters. NAFDAC has monopolized the regulation and control of food safety matters lo pharmacists, failing to accede and concede to the unique roles of public health veterinarians, which has been clearly elucidated in the Animal Disease Control Decree 10 of 1988. In the light of present universal public health realities, an appropriate review and strengthening of the Animal Disease Control Act (Decree 10) of 1988 and the need for bill to create in the Federal Ministry of Agriculture, a Nigerian equivalent of the US Department of Agriculture's Food Safely and Inspection Service (FSIS) arc called for while Public health veterinarian in Nigeria should brace up to adequately respond to the prevailing Food Safety challenge.